Three anti-inflammatory polysaccharides from Lonicera japonica Thunb.: insights into the structure-function relationships - Yu Liu; Hongjing Dong; Dongxiao Sun-Waterhouse; Wenwen Li; Bin Zhang; Jinqian Yu; Zhichang Qiu; Zhenjia Zheng (Food Science and Human Wellness)
This study demonstrates the feasibility of producing three polysaccharides (neutral LJP -1, acidic LJP-2 and acidic LJP-3) with significant in vitro and in vivo anti-inflammatory activities from the flowers of Lonicera japonica. The three polysaccharides differed in chemical composition, molecular weight (Mw) distribution, glycosidic linkage pattern, functional groups and morphology. They exhibited excellent protective effects (in a dose-dependent manner) in lipopolysaccharide-injured RAW264.7 macrophages and CuSO4-damaged zebrafish via reducing NO production and inhibiting the overexpressions of inflammation-related transcription factors, inflammatory proteins and cytokines in the NF-κB/MAPK signaling pathways. Their anti-inflammatory effects varied owing to their different molecular characteristics and chemical compositions. Overall, LJP-2 at 400 μg/mL was the most effective. LJP-2 consisted mainly of →5)-α-L-Araf (1→, →4)-α-L-GalpA (1→ and →2)-α-L-Rhap (1→ residues with terminal T-β-D-Glcp. Thus, honeysuckle flowers are good sources of anti-inflammatory polysaccharides, and precise fractionation enables the production of potent anti-inflammatory agents for the development of functional foods and healthcare products.